Traffic Related Injuries from a Trauma Registry: Pattern and Outcome - Ibeanusi, Sydney E.; Diamond, Tamunokro E. (Nigerian Journal of Orthopaedics and Trauma, 2018)
Background: Road traffic trauma is a leading cause of death and disability in persons aged below 45 years. It has a global distribution, but its incidence and impact are greatest in low‑ and middle‑income countries. Establishing pattern of injuries arising from traffic collisions and the outcome of such injuries helps to plan interventions effective in reducing the incidence, mortality and morbidity from road traffic crashes (RTCs). Methods: Data of patients presenting with injuries from RTCs from a trauma registry which was prospectively developed from a dedicated trauma centre based in south‑south region of Nigeria were collected and analysed. Descriptive and inferential statistics of data of patients with injuries resulting from traffic collisions from the trauma registry seen between 1 January 2007 and 31 December 2012 were generated and presented. Results: During the study period, 61,820 (65.6%) patients presented with injuries resulting from RTCs. Majority of the patients were males aged between 20 and 40 years. Most of the patients (n = 51,620, 83.5%) presented after 1 h of the incident. Only about 5.2% (3215) of the victims were brought to the hospital by some type of ambulance. Majority of the patients had of injury involving the exterior in 77% (n = 47,601) and the extremities in 23.5% (n = 14,500) of the cases, respectively, but mortality was <1%. Conclusion: RTCs contributed significantly to the trauma burden in Port Harcourt, Nigeria. Delayed presentation, and improper transportation methods of injured victims to hospitals, may have contributed to poor outcome of some of the injuries.